Perspectives Sufism Social In Remediation Crisis Moral In Humans Modern - Ishmah, Nihayatul (http://jagadalimussirry.com/, 2020)
Urgency science of Sufism is to foster moral self- humans both in the affairs of the world and the affairs of the Hereafter later . The problem is related to morals or behavior possessed by humans. Modern society will tend to hold opinions and behave freely because all humans have the same rights and do not distinguish degrees or power. Such freedom can affect changes in human behavior which can also lead to deviant behavior in terms of religion. This freedom encourages society to be individualistic, materialistic and hedonism. The implementation of Sufism can be applied as a moral guidance for modern society to keep on doing world worship with the worship of the hereafter as well. Balance in life will happen well.